Difference between Burley Tobacco and Flue-Cured Tobacco in Nitrate Accumulation and Chemical Regulation of Nitrate and TSNA Contents - Yafei Li; Hongzhi Shi; Huijuan Yang; Jun Zhou; Jing Wang; Ruoshi Bai; Dongya Xu (Journal of Chemistry)
Tobacco-specific nitrosamines (TSNAs) are harmful carcinogens, with nitrate as a precursor of their formation. Nitrate content is considerably higher in burley tobacco than in flue-cured tobacco, but little has been reported on the differences between types of nitrate accumulation during development. We explored nitrate accumulation prior to harvest and examined the effects of regulatory substances aimed at decreasing nitrate and TSNA accumulation. In growth experiments, nitrate accumulation in burley and flue-cured tobacco initially increased but then declined with the highest nitrate content observed during a fast-growth period. When treating tobacco crops with molybdenum (Mo) during fast growth, nitrate reductase activity in burley tobacco increased significantly, but the NO3-N content decreased. These treatments also yielded significant reductions in NO3-N and TSNA contents. Therefore, we suggest that treatment with Mo during the fast-growth period and a Mo-Gfo (Mo-glufosinate) combination at the maturity stage is an effective strategy for decreasing nitrate and TSNAs during cultivation.